General Map of North America from the best Authorities - Russell, John fl. 1733-1795 (1785)
18th century Copper engraving. Printed in cartouche in lower left corner: “A General Map of North America from the best Authorities.” Handwritten in title cartouche: "1790" Printed beneath cartouche: “Russell Sculpt.” Printed beneath cartouche in lower left corner outside border: ”Longitude West from London.” Includes Nootka Sound as “Nootka or King Geo. Sound” as well as “Entrance Juan de Fuco.” Of note, depicts “River of the West” originating in the Pacific Northwest.” Northern California is labeled as New Albion or "Nova Albion." The northwestern portion of the United States is labeled as Quivira or "Qvivira." Fox(e) Island and Southampton Island are shown between Hudson Bay and Baffin Bay with no indication of the existence of Baffin Island. Prime meridian: London. [W 180 degrees – W 30 degrees / N 85 degrees – N 10 degrees] Scale: c.a. 1:42,000,000. John Russell was an engraver and draughtsman for many cartographers including Dalrymple (1744-5). He also contributed to a number of published works including Guthrie's "System of Geography" (1785), "American Atlas (1795) and Burney's "Voyages" (1813). Russell produced a similar copy of this map titled, "A General Map of North America drawn from the Best Sources," published in 1794 (Tooley, 553; Wheat, 242). This map reflects a trend in mapmaking towards less use of ornate decoration. Source(s): Tooley, Ronald Vere. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979. Wheat, Carl I. "Mapping the Transmississippi West." Volume 1. San Francisco: Institute of Historical Cartography, 1957.